A Study on the Sustainable Solution for the Construction Industry: Mitigating Air, Water, Soil, and Noise Pollution through Pre-Engineered Structures - Mlayng, Abraham; Mgonja, Christopher (Journal of Progress in Civil Engineering, 2026)
Problem: Construction Industry is proliferating significantly to accommodate the rising population in urban and rural areas globally, responsible for Environmental Pollution accounting for 27% of air pollution, 40% of water bodies’ contamination along with Rapid Groundwater depletion and 50% of landfill waste also subsequently key issues includes Habitat loss, ecosystem disruption, waste generation and Noise pollution. Sustainable construction practices are essential to mitigate these impacts. We conducted this research to identify the sources and came up with a sustainable solution to protect natural resources and promote healthier environment for future generations. Solution: Pre-fabricated construction can mitigate environmental pollution in the construction industry by reducing carbon emissions, Controlling emissions of PM2.5 and PM10, minimizing water usage and wastage, minimizing waste generation and improving energy efficiency. Factories can manufacture components in controlled environments, leading to reduced energy usage and emissions compared to on-site construction. Pre-fabricated components can also be designed to optimize material use and incorporate recycled content, further minimizing the environmental impact. This research suggests that pre-casting\pre -fabrication can lead to a 10% carbon reduction for every cubic meter of concrete compared to traditional methods. Specific indicators are developed to evaluate projects’ sustainability performance with various levels of prefabrication.